Indonesia’s Omnibus Law and Protection of Labor Rights - Dewi, Mira Nila Kusuma; Basir, Abd. (Amsir Law Journal, 2023)
Indonesian constitution (Undang-Undang Dasar Republik Indonesia of 1945) regulates that Everyone has the right to choose a job and work and receive omnibus law on job creation is enacted in Indonesia. In 2023, the Government has enacted Law Number 6 of 2023 concerning Determination of Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation into Law or so-called Omnibus Law on Job Creation. The objective of this research is to analyze labor rights protection in Omnibus Law Indonesia. Research method used in this research is normative research, using statute approach and conceptual approach. It is analyzed using descriptive method. The result of this research is that the Ominbus Law Indonesia has not given labor rights protection fully in connection with issues of termination of employment, criminal sanctions for entrepreneurs, foreign workers, wages, severance pay, lifelong contract employees, lifetime outsourcing, working time, leave and wages for leave, health insurance and pension guarantees for outsourcing contract workers. This is because lack of lack of community involvement in the formation of laws. Therefore, it needs to be amended. ___ References Books with an author: Sunaryati, H. (1994). Penelitian Hukum di Indonesia pada Akhir Abad ke-20. Bandung: Alumni. Journal articles: Ali, M. F. (2021). Efektivitas Omnibuslaw dalam Pembangunan Investasi (Studi Kasus Perusahaan Tesla. Inc). Jurnal Syntax Transformation, 2(10), 1447-1464. Asmani, N. I., & Fauzi, A. M. (2021). Penolakan Omnibus Law Menurut Paradigma Sosiologi Hukum dan Teori Konflik. Jurnal Justisia: Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 6(1), 102-112. Fitryantica, A. (2019). Harmonisasi Peraturan Perundang-Undangan Indonesia melalui Konsep Omnibus Law. Gema Keadilan, 6(3), 300-316. Kartikasari, H., & Fauzi, A. M. (2021). Penolakan Masyarakat Terhadap Pengesahan Omnibus Law Cipta Kerja dalam Perspektif Sosiologi Hukum. Doktrina: Journal of Law, 4(1), 39-52. Mahersaputri, R. A., & Apriani, R. (2022). Dampak Undang-Undang Omnibus Law terhadap Iklim Investasi di Indonesia. Jurnal Justitia: Jurnal Ilmu Hukum dan Humaniora, 9(3), 1353-1361. Purwanda, S., & Dewi, M. N. K. (2020). The Effects of Monism and Pluralism on Legal Development of a Nation. Amsir Law Journal, 2(1), 21-26. Putra, A. (2020). Penerapan Omnibus Law Dalam Upaya Reformasi Regulasi. Jurnal Legislasi Indonesia, 17(1), 1-10. Rahman, M. S. (2018). Breach of Contract and the Sanction in Agreements to Outsource by the Government: Juridical Analysis of Article 1601 B of the Indonesian Civil Code. International Journal of Innovative Research & Development, 7(12). Siregar, A. A. (2022). Legal Studies on Omnibus Law Issues in Indonesia. International Asia of Law and Money Laundering (IAML), 1(4), 270-278. Tarring, A. D., & Karim, K. (2022). Civil Evidence Using Electronic Documents in Indonesia. International Journal of Multicultural and Multireligious Understanding, 9(11), 250-256. Utomo, P. (2020). Omnibus Law: Dalam Perspektif Hukum Responsif. Nurani Hukum, 2(1), 33-41. Wole, B. D., Purwatiningsih, A., & Kamaluddin, K. (2021). Iklim Investasi dalam Penyelesaiannya Penerapan Omnibus Law. Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 3(2), 118-127. World Wide Web: Deny, S. (2023). UU Omnibus Law Jadi Sorotan di Konferensi Buruh Internasional. Available online from: https://www.liputan6.com/bisnis/read/5328230/uu-omnibus-law-jadi-sorotan-di-konferensi-buruh-internasional . Farisa, F. C. (2023). Jejak Kontroversi UU Cipta Kerja: Disahkan Kilat, Perppu Diketok meski Banjir Penolakan. Available online from: https://nasional.kompas.com/read/2023/03/21/14021541/jejak-kontroversi-uu-cipta-kerja-disahkan-kilat-perppu-diketok-meski-banjir . Mediana. (2023). UU Cipta Kerja Bahasan Konferensi Buruh Internasional. Available online from: https://www.kompas.id/baca/ekonomi/2023/06/11/kelompok-pekerja-tetap-menentang-keberadaan-uu-cipta-kerja . Sahbani, A. (2022). MK Kembali Kandaskan Pengujian Materil UU Cipta Kerja. Available online from: https://www.hukumonline.com/berita/a/mk-kembali-kandaskan-pengujian-materil-uu-cipta-kerja-lt61f115a3b101c/ . Sari, A. R. (2023). Partai Buruh dan Organisasi Serikat Buruh Lakukan Judicial Review UU Cipta Kerja ke MK. Available online from: https://bisnis.tempo.co/read/1721917/partai-buruh-dan-organisasi-serikat-buruh-lakukan-judicial-review-uu-cipta-kerja-ke-mk .